Imaging of CO2 bubble plumes above an erupting submarine volcano, NW Rota‐1, Mariana Arc. (25th November 2014) - Chadwick, William W.; Merle, Susan G.; Buck, Nathaniel J.; Lavelle, J. William; Resing, Joseph A.; Ferrini, Vicki
Abstract NW Rota‐1 is a submarine volcano in the Mariana volcanic arc located ∼100 km north of Guam. Underwater explosive eruptions driven by magmatic gases were first witnessed there in 2004 and continued until at least 2010. During a March 2010 expedition, visual observations documented continuous but variable eruptive activity at multiple vents at ∼560 m depth. Some vents released CO2 bubbles passively and continuously, while others released CO2 during stronger but intermittent explosive bursts. Plumes of CO2 bubbles in the water column over the volcano were imaged by an EM122 (12 kHz) multibeam sonar system. Throughout the 2010 expedition numerous passes were made over the eruptive vents with the ship to document the temporal variability of the bubble plumes and relate them to the eruptive activity on the seafloor, as recorded by an in situ hydrophone and visual observations. Analysis of the EM122 midwater data set shows: (1) bubble plumes were present on every pass over the summit and they rose 200–400 m above the vents but dissolved before they reached the ocean surface, (2) bubble plume deflection direction and distance correlate well with ocean current direction and velocity determined from the ship's acoustic doppler current profiler, (3) bubble plume heights and volumes were variable over time and correlate with eruptive intensity as measured by the in situ hydrophone. This study shows that midwater multibeam sonar data can be used to characterize the level of eruptive activity and its temporal variability at a shallow submarine volcano with robust CO2 output.